A Study on the Establishment of Integrated Health Information Service Model of Public Libraries - Noh, Younghee (International Journal of Knowledge Content Development & Technology, 2022)
Currently, it is not easy for most domestic public libraries to collect and provide reliable health information services on their own. Health information is distributed or professional, making it inconvenient for users to use. Based on the implications derived from the case study, the Library Health Information Integration Service Model was proposed as a specialized information service. The model consists of a composition shared by librarians, health and medical experts, and users, focusing on library websites that provide integrated health information integration services, and has the following features. First, it provides health and medical information on a specialized subject. Second, it provides integrated health and medical information services provided in various ways. Third, librarians and health and medical experts work together to provide information services. Fourth, users can freely use health information integration services online and offline. The model presented in this study means that libraries can play a leading role in health information integration services to increase the utilization rate of public libraries and further contribute to librarians serving as experts in health information services.